2018
DOI: 10.1097/aog.0000000000002694
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Spontaneous Abortion After Inadvertent Human Papillomavirus Vaccination in Pregnancy

Abstract: Inadvertent 4vHPV exposure during or peripregnancy was not significantly associated with an increased risk of spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 20 publications
(28 reference statements)
5
30
0
3
Order By: Relevance
“…The results of this study are in line with those of initial pre-licensure 9vHPV clinical study data, which did not indicate overall increased risks of spontaneous abortion, stillbirth, or major birth defect when 9vHPV was inadvertently administered to pregnant women, compared to 4vHPV, although risk of spontaneous abortion was higher among women administered 9vHPV compared to 4vHPV (20.0% vs. 9.2%) within 30 days of pregnancy initiation (5, 13). They are also in line with prior studies assessing AEs following 4vHPV administration during pregnancy that have not revealed any concerning patterns of pregnancy-specific or infant/neonatal outcomes following vaccine administration (812). An analysis of prospective reports of vaccine exposure during pregnancy from the United States, Canada, and France submitted to the vaccine manufacturer (Merck and Co., Inc.) registry did not find any concerning patterns of spontaneous abortions, fetal deaths, or birth defects following vaccine administration (9).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are in line with those of initial pre-licensure 9vHPV clinical study data, which did not indicate overall increased risks of spontaneous abortion, stillbirth, or major birth defect when 9vHPV was inadvertently administered to pregnant women, compared to 4vHPV, although risk of spontaneous abortion was higher among women administered 9vHPV compared to 4vHPV (20.0% vs. 9.2%) within 30 days of pregnancy initiation (5, 13). They are also in line with prior studies assessing AEs following 4vHPV administration during pregnancy that have not revealed any concerning patterns of pregnancy-specific or infant/neonatal outcomes following vaccine administration (812). An analysis of prospective reports of vaccine exposure during pregnancy from the United States, Canada, and France submitted to the vaccine manufacturer (Merck and Co., Inc.) registry did not find any concerning patterns of spontaneous abortions, fetal deaths, or birth defects following vaccine administration (9).…”
Section: Discussionsupporting
confidence: 89%
“…However, some women of childbearing age might be inadvertently exposed during catchup vaccination (6, 8, 9). Studies following 2vHPV and 4vHPV administration during pregnancy did not reveal concerning patterns of pregnancy-specific or infant/neonatal outcomes following vaccine administration (812). Initial pre-licensure clinical study data did not indicate an overall increased risk of spontaneous abortion, stillbirth or major birth defects when 9vHPV was inadvertently administered to pregnant women, compared to 4vHPV (5, 13).…”
Section: Introductionmentioning
confidence: 90%
“…In diesen Studien zeigte sich, dass eine Impfung selbst kurz vor oder während einer Schwangerschaft keine negativen Auswirkungen auf die Entwicklung des Kindes oder den Schwangerschaftsverlauf hat [10] [11]. Ebenso wenig sind teratogene Effekte zu befürchten [12].…”
Section: Rolle Der Hpv-infektion In Der Hebammenarbeitunclassified
“…Die bisherigen Daten zu den Nebenwirkungen des quadrivalenten Impfstoffes decken sich zudem mit denen für den nonavalenten HPV-Impfstoff, der gegen die Infektion mit neun bei uns weit verbreiteten HPV-Typen (HPV 6,11,16,18,31,33,45,52,58) schützt.…”
Section: Rolle Der Hpv-infektion In Der Hebammenarbeitunclassified
“…Reported only in HPV vaccine 으나, Kharbanda 등(2018)은 임신부 대상 코호트 연구에서 임 신 중 4가 HPV 백신 접종과 자연 유산 사이에 유의한 관련성 이 없다고 밝혔다 10,20). 혈관염의 경우 허가사항에 반영되어 있지 않았으나, HPV 백신 접종 후 혈관염 증례 보고와 VAERS 데이터베이스를 이용한 환자-대조군 연구에서 HPV 4 가 백신과 혈관염 사이에 관련성이 있다는 보고가 존재하므로 (OR=4.00; 95% CI 1.01-16.40) 인과성을 평가한 추가적인 연 구가 필요하겠다 21,22).…”
unclassified